Dopaminergic induced changes in cognitive and motor processing in Parkinson's disease: an electrophysiological investigation. Issue 7 (July 1991) - Prasher, D; Findley, L
Abstract : Event-related potentials and reaction time measures to auditory discrimination tasks of graded difficulty were used to separate cognitive from motor processing time in 27 patients with newly diagnosed, previously untreated Parkinson's disease and later on optimal levodopa treatment. Before treatment event-related potential P3 and task performance were normal but the reaction time was prolonged compared with age matched controls. After treatment P3 latency was significantly prolonged and the reaction time reduced suggesting a dopamine induced dissociation between cognitive and motor processing. In early Parkinson's disease cognitive processing time remains normal but the motor processing time is prolonged. Dopamine replacement is followed by significantly reduced motor processing time despite increased cognitive processing time. Motor processing may reflect the dopamine status of the putamen whereas dopaminergic over-stimulation of other regions may adversely affect cognitive processing in patients treated with levodopa.